2009
DOI: 10.1021/jf8033623
|View full text |Cite
|
Sign up to set email alerts
|

Usefulness of Fluorescence Excitation−Emission Matrices in Combination with PARAFAC, as Fingerprints of Red Wines

Abstract: The possibility of using front-face fluorescence spectroscopy to characterize red wines was investigated, and a tentative identification of their main fluorescent components was attempted. Fifty-seven red wine samples from different origins were included in the present study. Their fluorescence excitation-emission matrices (EEMs) were registered directly on 3-mL aliquots of untreated samples. The assayed excitation and emission ranges were 245-340 and 300-500 nm, respectively. The set of 57 EEMs was analyzed b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
72
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 119 publications
(79 citation statements)
references
References 22 publications
7
72
0
Order By: Relevance
“…For example, Dufour et al, employed both excitation and emission spectra for French and German wine classification (Dufour, Letort, Laguet, Lebecque, & Serra, 2006), and Sádecká et al reported the classification of brandies and wine distillates using total luminescence and synchronous fluorescence spectra (Sádecká, Tóthová, & Májek, 2009), but only first-order data and algorithms were used in an unsupervised manner in both cases. On the other hand, Ariado-Rodrigues and collaborators employed EEM and PARAFAC for fingerprinting of red wines (Airado-Rodríguez, Galeano-Díaz, Durán-Merás, & Wold, 2009) and quality control in the wine industry (Airado-Rodríguez, Durán-Merás, Galeano-Díaz, & Wold, 2011). Interestingly, and different from the present report, an unsupervised approch was used in both reports.…”
Section: Introductionmentioning
confidence: 71%
“…For example, Dufour et al, employed both excitation and emission spectra for French and German wine classification (Dufour, Letort, Laguet, Lebecque, & Serra, 2006), and Sádecká et al reported the classification of brandies and wine distillates using total luminescence and synchronous fluorescence spectra (Sádecká, Tóthová, & Májek, 2009), but only first-order data and algorithms were used in an unsupervised manner in both cases. On the other hand, Ariado-Rodrigues and collaborators employed EEM and PARAFAC for fingerprinting of red wines (Airado-Rodríguez, Galeano-Díaz, Durán-Merás, & Wold, 2009) and quality control in the wine industry (Airado-Rodríguez, Durán-Merás, Galeano-Díaz, & Wold, 2011). Interestingly, and different from the present report, an unsupervised approch was used in both reports.…”
Section: Introductionmentioning
confidence: 71%
“…Any data set that can be modeled adequately with PARAFAC can be thus also be modeled by Tucker-3 or two-way PCA. PARAFAC has already been used in many food systems including meat (Moller, Parolari, Gabba, Christensen, & Skibsted, 2003), fish oil (Pedersen, Munck, & Engelsen, 2002), milk (Boubellouta & Dufour, 2008), cheese (Christensen, Povlsen, & Sorensen, 2003), sugar (Bro, 1999), beer (Sikorska et al, 2008), red wine (Airado-Rodriguez, Galeano-Diaz, Duran-Meras, & Wold, 2009) and oils (Dupuy et al, 2005;Guimet, Ferré, & Boqué, 2005a;Guimet, Ferré, Boqué, & Rius, 2004;Guimet, Ferre, Boque, Vidal, & Garcia, 2005b;Sikorska et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…This approach has been implemented successfully for the quantitative analysis of various complex biogenic samples from, e.g. wine [50], milk [40,51], food [5,52,53], and cell culture media [4,35,54]. In many of these applications, there are generally multiple fluorophores present, often at high concentration.…”
Section: Inner Filter Effects (Ife)mentioning
confidence: 99%